Doping-induced photocatalytic activity and hydrogen evolution of ZnS: V nanoparticles. Issue 18 (15th September 2021) - Poornaprakash, B.; Park, Herie; Subramanyam, K.; Vattikuti, S.V. Prabhakar; Devarayapalli, Kamakshaiah Charyulu; Nam, Seung Hyun; Kim, Y.L.; Pratap Reddy, M. Siva; Hahm, Myung Gwan; Minnam Reddy, Vasudeva Reddy
Abstract: In the present study, we fabricate the ZnS: V (0, 2, 4, and 6 at%) nanoparticles (NPs) using the chemical-refluxing technique. We analyzed these samples based on structural, optical, magnetic, degradation, and hydrogen evolution properties. Comprehensive analyses of the chemical, structural, and optical measurements show that the vanadium (V) ions occupied the Zn host site without altering their original structure and without forming new phases. We confirmed the paramagnetic nature of the doped samples via magnetic measurements. We examined the photocatalytic properties of the fabricated NPs by the degrading Rhodamine-B (RhB) dye in an aqueous solution under the ultraviolet (UV) light, and the ZnS: V of 2 at% displayed higher degradation efficiency than the other samples. Moreover, 2 at% ZnS: V (sample showed a higher H2 evolution rate (1140 μmolg −1 h −1 ) than the other samples and was 17 times greater than that of pure ZnS lattice. The observed efficient photocatalytic organic pollutant degradation and better hydrogen fuel evolution in 2 at% ZnS: V sample could be due to the presence of a large surface area, creation of more defect sites, dislocation sites of the prepared compound, generation, and the presence of a huge number of charge carriers due to the substitution of V-dopant in the Zn host site and non-recombination rate of charges.